Molecular Docking and Dynamics of a Series of Aza-Heterocyclic Compounds Against Penicillin-Binding Protein 2a of Methicillin-Resistant Staphylococcus aureus - Karen Astrid Ortiz-Vargas; Rsuini Uri Gutierrez-Aguilar; Judit Araceli Avina-Verduzco; Hugo A. Garcia-Gutierrez; Julio Cesar Ontiveros-Rodriguez; Rafael Herrera-Bucio; Pedro Navarro-Santos (Chemistry Proceedings)
Staphylococcus aureus is a Gram-positive bacterium known to cause mild to severe and potentially fatal infections such as endocarditis, sepsis, meningitis, pneumonia, and bacteremia, among others. The methicillin-resistant strain of Staphylococcus aureus (MRSA) arose because the bacterium acquired an additional penicillin-binding protein by lateral gene transfer, known as penicillin-binding protein 2a (PBP2a). It is responsible for cross-linking peptidoglycan chains in the formation of the bacterial cell wall, and it is a deathly pathogen because it can infect almost all sites in the body; thus, the development of novel PBP2a inhibitors and the treatment of infections caused by this bacterium is vital. In this work, a systematic study of molecular docking and molecular dynamics was carried out to determine the stability of a set of ligands, aza-heterocyclic compounds, against PBP2a, analyzing their RMSD, H-bonds interactions, and binding free energy. In addition, the pharmacokinetic properties are discussed, finding that our proposed ligand 5 is the most promising compound in terms of stability and energetic results.